Teacher Quality, Facilities, and Cost: A Discourse Analysis of Quora Narratives on Public vs. Private Schools in Indonesia - Muhammad Saefulloh (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2026)
This study examines public perceptions of public versus private schools in Indonesia using user-generated content from Quora. Parents face a difficult decision when choosing between Indonesia's large number of public (7,396) and private (7,049) senior high schools. Thirty answers to the question "Apa perbedaan yang signifikan antara sekolah negeri dan sekolah swasta?" (What are the significant differences between public and private schools?) were analyzed using discourse analysis to identify the key distinctions between these two types of schools. The investigation identifies three key factors that influence the narratives around these two kinds of schools: teacher quality and professionalism, school facilities, and cost and accessibility. The results show that public schools are regarded for their affordability and socioeconomic inclusion, whereas private schools are perceived to offer better facilities and more qualified teachers. This study contributes to the ongoing conversations around educational equity and quality by highlighting the influence of online platforms on educational decision- making and the complexity of the Indonesian educational system.